Modeling Bedoyo Majapahit Dance Motion Using HMM Emission Families - Anang Kukuh Adisusilo; Emmy Wahyuningtyas; Teguh Pribadi Ikhsan (Jurnal Teknologi Informasi dan Pendidikan, 2026)
This study investigates three types of emission families in Hidden Markov Models (HMMs) for reconstructing Bedoyo Majapahit dance motion captured using a markerless system. The recorded skeleton data, consisting of 3,341 frames and 33 joints per frame, were normalized and reduced into a 30-dimensional latent space using Principal Component Analysis (PCA). Three emission variants were evaluated: single-Gaussian HMM, Gaussian-mixture HMM (GMM-HMM), and Multinomial HMM. The evaluation employed a tri-metric scheme consisting of Mean Squared Error (MSE), Dynamic Time Warping (DTW), and Fréchet distance to measure reconstruction fidelity. The experimental results showed that GMM-HMM consistently outperformed the other two models, achieving the lowest reconstruction error and the closest alignment to the original temporal and geometric motion profiles. The Gaussian HMM demonstrated moderate performance but tended to underestimate motion amplitude, while the Multinomial HMM produced the weakest results due to the discretization of continuous pose data. These findings indicate that multimodal emission functions provide a more expressive representation for continuous dance motion. The study highlights the suitability of GMM-HMM for traditional dance preservation through computational modeling and contributes to the development of digital motion archiving for cultural heritage.